An Overview of Regulatory Authorities in Pharmaceutical’s - Ovhal Prabhakar; Chaudhari Bharatee (Asian Journal of Pharmaceutical Research and Development, 2026)
Regulatory authorities have an obligation to protect the public’s health by ensuring that drug products are safe, effective, and of good quality. These agencies are responsible for drug development, clinical trials, manufacturing practices, product approvals, and monitoring after marketing. Leading worldwide regulatory bodies, including the United States Food and Drug Administration (FDA), European MedicinesAgency (EMA), Central Drugs Standard Control Organization (CDSCO) in India, Pharmaceuticals and Medical Devices Agency (PMDA) in Japan, and National Medical Products Administration of China (NMPA), have developed different frame works or guidelines for drug regulation. Although they serve the same purpose, differences in what needs to be approved, time, and regulatory requirements make gaining global access to drugs more difficult. International harmonization, as pursued by the International Council for Harmonization (ICH and World Health Organization (WHO)n),aims to overcome these gaps and ensure a high degree of regional comparability. This review provides insights into the organization, functions, and comparative features of the major regulatory bodies, as well as current challenges and prospects, such as digital health, artificial intelligence (AI), and patient-centred approaches. Enhanced global regulatory coordination is essential for accelerating innovation and enabling the highest levels of patient safety.